Partnering Strategies of Organizational Networks in Complex Environment of Disaster in the Centralized Political Context - Zhigang Tao; Haibo Zhang (Complexity)
Organizational networks are a widely used approach to deal with the “wicked problems” of disasters. However, current studies are insufficient in examining what strategies organizations actually employ to select partners in a complex environment of disaster, particularly in the centralized administrative context. This case study uses exponential random graph models (ERGMs) to explore different partnering strategies that organizations used to form organizational networks in response to the Tianjin Port blast, a well-known disaster in China. Results demonstrate that participating organizations prefer (a) the bonding structure strategy to form “reciprocity” and “transitive clustering,” (b) the power concentration strategy to work with popular organizations, and (c) the homophily strategy to work with similar attribute organizations. However, contextual backgrounds influenced organizational attributes and strategies. This study discusses the implications of the findings and offers recommendations for enhancing collaboration among organizations.